Review of David L. Schindler's Beyond mechanism: the universe in recent Catholic thought - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 1987)
This worthy volume contains the responses of four Catholics and one non-Catholic to the philosophical views of the physicist David Bohm. The central concept is that of the one "implicate order" unfolded into the many "explicate order." The analyses are stimulating but not definitive.
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: mechanism; metaphysics; Catholic theology; Bohm, David; implicate order; explicate order